Correctional personnel attitudes toward crime causation: free will or determinism? - Rhineberger, Gayle M., author; Turner, Ronny E., committee member (Colorado State University. Libraries, 1998)
For the past several decades interest in correctional personnel has grown steadily. However, little has been written on their attitudes toward crime causation. This study analyzes the results of a survey given to 271 correctional personnel. Using a free will/determinism dichotomy, correctional personnel attitudes toward crime causation are discussed. An analysis of the effects personal (e.g. age, gender) and occupational (e.g. years of correctional experience) characteristics have on predicting how personnel view crime causation is provided. Perceptions of correctional staff on how other members of the criminal justice system (e.g. police, society, judges, Department of Corrections) view crime causation is also discussed.
Keywords: Correctional personnel -- Attitudes; Criminal behavior